A five-year-old boy with anaphylaxis reaction to gadolinium-based MR contrast medium: a case report - Seung Hun Woo; Jung Bum Han; Tae Young Ahn; Jung Yun Bae (BMC, 2024)
Abstract Magnetic resonance imaging (MRI) is one of the most widely used tests in orthopedic areas. Gadolinium-based magnetic resonance (MR) contrast media are commonly used for MRI tests. They are known to be safe with little side effects and low incidence of acute adverse reactions. Although not common, immediate hypersensitivity reaction can occur in some patients after administration of gadolinium-based MR contrast media, causing skin rash, vascular edema, dyspnea, abdominal pain, hypotension, altered mental status, cardiopulmonary arrest, and even death. During a knee joint MRI test in a 5-year-old boy, anaphylaxis, a serious symptom, occured after injecting gadolinium-based MR contrast medium. Here we report this case along with a literature review.